Brain Dominance Learning Styles for Secondary School Students Distinguished and Ordinary (Journal of the College of Education for Women, 2019)
The current research aims at detecting Brain Dominance Learning Styles distinguishedand ordinary secondary school students (males and females).The researcher adopted Torrancemeasure, known as ‘the style of your learning and thinking to measure Brain DominanceLearning Styles’, the codified version of Joseph Qitami (1986); picture (a). The researcherverified the standard properties of tool. The final application sample was 352 distinguishedand ordinary students; 176 distinguished male and female students and 176 ordinary male andfemale students at the scientific fifth level of secondary school from schools in the province ofBaghdad, AL- KarKh Education Directorates in the First and Second . and who have beenselected in a stratified random sampling . After the application the tool of research andanalysis of the data statistically by using statistical methods ( Chi- Square, ,GuttmanCorrelation), the Researcher arrived at the following results:1.The right learning style is the dominant brain style among Individuals the research sampleApplied .2.The presence of statistically significant differences in the right Brain Dominance LearningStyle among the sample Individuals at distinguished and ordinary in favor of distinguishedstudents .3. The lack of statistically significant differences in the Brain Dominance Learning Styles canbe attributed to the sex variable.